Pengaruh Penerapan Sistem Administrasi Perpajakan Modern terhadap Kepatuhan Wajib Pajak (Survey Terhadap Kantor Pelayanan Pajak Pratama Bandung Bojonagara) - Sinta Setiana; Tan Kwang En; Lidya Agustina (Jurnal Akuntansi)
Efforts through programs and activities of tax administration reform are realized through the implementation of modern tax administration system is intended to encourage taxpayer compliance.